Criminal courts: a contemporary perspective - Hemmens, Craig (SAGE, 2017)
Introduction : law and the judicial function -- Sources of law -- Types of law -- Court organization and structure -- Specialized courts -- Prosecutors -- Defense attorneys -- Judges -- Criminal defendants and crime victims -- The jury -- Pretrial procedures -- The criminal trial -- Sentencing -- The appellate process